miR-139-5p and miR-451a as a Diagnostic Biomarker in LUSC - Gao B; Li R; Song X; Hu S; Yang F (Dove Medical Press, 2023)
Bo Gao,1,* Rui Li,2,* Xiaojia Song,3 Shan Hu,4 Fengmei Yang4 1Departments of Laboratory Medicine, Taihe Hospital, Hubei University of Medicine, Shiyan, Hubei, 442000, People's Republic of China; 2Departments of Medical office, Taihe Hospital, Hubei University of Medicine, Shiyan, Hubei, 442000, People's Republic of China; 3Shiyan Prefecture Center for Disease Control and Prevention, Shiyan, Hubei, 442000, People's Republic of China; 4Departments of Obstetrics and Gynecology, Taihe Hospital, Hubei University of Medicine, Shiyan, Hubei, 442000, People's Republic of China*These authors contributed equally to this workCorrespondence: Fengmei Yang, Email 29256175@qq.comBackground: Lung squamous cell carcinoma (LUSC) is a type of lung cancer that originates from segmental or subsegmental bronchial mucosa. There is evidence that miRNA plays an important role in the occurrence and progression of tumors.Methods: In this study, plasma samples of patients with early LUSC and healthy volunteers were subjected to miRNA sequencing, and the levels of differentially expressed miRNAs (DEMs) in LUSC tissues were analyzed using R language. Cox regression and Kaplan-Meier (K-M) survival curve analyses were performed to determine the relationship between DEMs and prognosis in LUSC, and PCR method was verified for the plasma expression level of DEMs in patients with LUSC. The levels of CYFRA21-1 and SCC-Ag in plasma were measured, and area under curve (AUC) was used to evaluate the diagnostic value of the DEMs.Results: A total of 21 DEMs were screened out by sequencing. The expression levels of DEMs in tissue samples in the TCGA database were analyzed, and four DEMs with consistent expression levels were further screened from plasma and tissue samples. Regression analysis and K-M curve were performed to select two DEMs (miR-139-5p, miR-451a) that were correlated with the prognosis. PCR verification results showed that the levels of miR-451a and miR-139-5p were low in patients, and the level of miR-139-5p in late stages III & IV with the patients of LUSC was higher than that in stages I & II. The AUC values of the four indicators (SCC-Ag, CYFRA21-1, miR-451a and miR-139-5p) in the diagnosis of LUSC, early and late cases were 0.884, 0.935 and 0.778, respectively.Conclusion: The detection of miR-139-5p and miR-451a levels in plasma has a certain potential in the non-invasive diagnosis, especially in patients with early stages of LUSC.Keywords: miR-139-5p, LUSC, miR-451a, diagnosis, prognosis